2019
DOI: 10.2494/photopolymer.32.585
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Donor-acceptor-type Polymers Comprising Alkoxy-substituted Bithiophene Units

Abstract: Two donor-acceptor-type conjugated polymers comprising alkoxy-substituted bithiophenes were synthesized by both direct C-H arylation polymerization and Stille-type polycondensation. Although these polymers contain the same components, i.e. two alkoxythiophene moieties and one benzothiadiazole moiety in a repeating unit, their optical and electrochemical properties were clearly different owing to their different regioregularities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…47 I. Imae et al reported that introduction of alkoxy groups could enhance the electron-donating nature of D-A polymers and reduce their oxidation potentials. [48][49][50][51] Here, in our work, with incorporating more electron rich 3,4-EDOT units, the onset oxidation potentials of the random copolymers reduced and the corresponding HOMO level of the random copolymers rised from À5.20, À5.07 to À4.95 eV for PDPP-EDOT-20, PDPP-EDOT-40 and PDPP-EDOT-50, respectively. The reduction peak for these polymers were decreased to lower potential as the content of EDOT units increased in the polymers.…”
Section: Electrochemical Propertiesmentioning
confidence: 59%
“…47 I. Imae et al reported that introduction of alkoxy groups could enhance the electron-donating nature of D-A polymers and reduce their oxidation potentials. [48][49][50][51] Here, in our work, with incorporating more electron rich 3,4-EDOT units, the onset oxidation potentials of the random copolymers reduced and the corresponding HOMO level of the random copolymers rised from À5.20, À5.07 to À4.95 eV for PDPP-EDOT-20, PDPP-EDOT-40 and PDPP-EDOT-50, respectively. The reduction peak for these polymers were decreased to lower potential as the content of EDOT units increased in the polymers.…”
Section: Electrochemical Propertiesmentioning
confidence: 59%